2017
DOI: 10.1074/mcp.m116.064675
|View full text |Cite
|
Sign up to set email alerts
|

A Two-pronged Binding Mechanism of IgG to the Neonatal Fc Receptor Controls Complex Stability and IgG Serum Half-life

Abstract: The success of recombinant monoclonal immunoglobulins (IgG) is rooted in their ability to target distinct antigens with high affinity combined with an extraordinarily long serum half-life, typically around 3 weeks. The pharmacokinetics of IgGs is intimately linked to the recycling mechanism of the neonatal Fc receptor (FcRn). For long serum half-life of therapeutic IgGs, the highly pH-dependent interaction with FcRn needs to be balanced to allow efficient FcRn binding and release at slightly acidic pH and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Several studies have suggested that the antigen binding fragment (Fab) can contribute to FcRn binding, 11,17–19 and a recent publication supports this hypothesis by demonstrating that the Fab region of an IgG can interact directly with FcRn. 16 Our hypothesis was additionally strengthened by recent publications by other groups showing a correlation between antibody charge and the FcRn affinity or PK of IgG molecules not influenced by target-mediated CL. 5,11,18,25,26 In the current study, we set out to further understand if Fab-containing domains can influence PK.…”
Section: Introductionsupporting
confidence: 65%
“…Several studies have suggested that the antigen binding fragment (Fab) can contribute to FcRn binding, 11,17–19 and a recent publication supports this hypothesis by demonstrating that the Fab region of an IgG can interact directly with FcRn. 16 Our hypothesis was additionally strengthened by recent publications by other groups showing a correlation between antibody charge and the FcRn affinity or PK of IgG molecules not influenced by target-mediated CL. 5,11,18,25,26 In the current study, we set out to further understand if Fab-containing domains can influence PK.…”
Section: Introductionsupporting
confidence: 65%
“…Results from Wang et al suggest that Fab charges cannot only influence the outcome of FcRn affinity chromatography but at the same time influence the outcome of SPR-based assays, depending on the chosen setup [19]. Correlations between FcRn affinity chromatography results of antibodies with differently charged Fab fragments and their in vivo PK were already established previously [4] and recent hydrogen-deuterium exchange (HDX) data supplemented by FcRn affinity chromatography data furthermore i ndicate that both interactions contribute to binding [37].…”
Section: Discussionmentioning
confidence: 68%
“…Further, the 250-helix residues demonstrated enhanced deuterium exchange at low pH in the absence of FcRn, suggesting that a pH-specific conformational change occurred within this region. 23,24 …”
Section: Resultsmentioning
confidence: 99%